Barrier Inhomogeneity of Pt/GaN Junctions with a Low-Temperature ALD Grown ZnO Interlayer - Hogyoung Kim; Ye Bin Won; Byung Joon Choi (Archives of Metallurgy and Materials)
Semiconducting GaN can realize high performance electronic and power devices owing to its high electron mobility and thermal conductivity where good metal-semiconductor contact is prerequisite. In this work, using thermal atomic layer deposition (ALD), ZnO interlayer was grown at 80°C on GaN and the Pt/ZnO/GaN heterojunctions were electrically characterized. The analyses on the current–voltage (I–V) and capacitance (C–V) data showed that the forward I–V conduction was involved with the inhomogeneous Schottky barrier. The higher density of interface states from I–V data than that from C–V data was attributed to nonuniform distribution of interface states. In addition, high density of interface states caused localized high electric field, caused higher Poole Frenkel emission coefficients than the theoretical one.